Histological and Histomorphometric Evaluation of Applying a Bioactive Advanced Platelet-Rich Fibrin to a Perforated Schneiderian Membrane in a Maxillary Sinus Elevation Model - Xin, Liangjing; Yuan, Shuai; Mu, Zhixiang; Li, Dize; Song, Jinlin; Chen, Tao (Frontiers in Bioengineering and Biotechnology, 2020)
Background Schneiderian membrane (SM) perforation is a major complication of maxillary sinus elevation with simultaneous bone grafting, yet under this scenario there is no standard biomaterial that maximizes favorable tissue healing and osteogenic effects. Purpose To compare the effect of advanced platelet-rich fibrin (A-PRF) and collagen membrane (CM) on a perforated SM with simultaneous bone grafting in a maxillary sinus elevation model. Materials and Methods After perforation of the SM was established, 24 animals were randomly divided into two groups: (i) group CM: CM and deproteinized bovine bone mineral (DBBM) (n = 12), (ii) group A-PRF: A-PRF and DBBM (n = 12). Radiographic and histological evaluations were performed at 1 and 4 weeks post-operation. Results At 1 week, an intact SM was found in group A-PRF. At each time point, the number of inflammatory cells at the perforated site was higher in group CM, and the area of new osteoid formation was significantly greater in group A-PRF (p < 0.0001). At 4 weeks, the osteogenic pattern was shown as from the periphery to the center of the sinus cavity in group A-PRF. Conclusion The higher elasticity, matching degradability, and plentiful growth factors of A-PRF resulted in a fully repaired SM, which later ensured the two osteogenic sources from the SM to generate significant new bone formation. Thus, A-PRF can be considered to be a useful bioactive tissue-healing biomaterial for SM perforation with simultaneous bone grafting.